THE EFFECT OF THE IMPLEMENTATION OF E-BUDGETING, FINANCIAL STATEMENT DISCLOSURE, AND INTERNAL CONTROL ON REGIONAL FINANCIAL MANAGEMENT TRANSPARENCY - Angga Vredi Nugroho; Sri Ayem (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Regional autonomy is the authority of a region in regulating, administering, and self-managing government and community affairs, including financial management. For this reason, the formulation of the problem of this study is whether e-budgeting affects the transparency of financial management, whether disclosure affects the transparency of financial management, and whether internal control affects the transparency of financial management. This study aims to see the effect of e-budgeting implementation, disclosure, and internal control on financial management transparency. The variables of this study are the implementation of e-budgeting, disclosure of financial reports, internal control and transparency of financial management. The sampling technique was purposive sampling. The data source uses primary data. The data collection method uses a questionnaire method. The analysis technique used is regression analysis with a significance level of 5%. The results showed that the implementation of e-budgeting and the disclosure of financial reports had a positive and significant effect on the transparency of financial management and internal control had no positive and significant effect on the transparency of financial management. This research contributes to government officials in demonstrating their role in promoting regional financial transparency.